Investigation of the relationship between joint position sense acuity and postural stability during lifting - Chua, Ming Wei (2014)
Stability of a person while carrying out lifting task is an important factor, as it allows the person to balance himself, prevent himself from falling and also reduce the risk of LBP. However, limited amount of studies were carried out on how proprioception affects lifting gait stability. The objective of this study is to investigate the relationship between joint position sense acuity and postural stability during lifting. Thirty-six participants of three different age groups (young, middle and old) were recruited to first undergo tests on joint position sense of three different joints (knee, ankle, hip), followed by lifting a box consisting of 10% of their body weight from the ground to their waist height for ten times. The results showed that as the error deviation in joint position sense of various joint increases among the older aged subjects, the COM displacement and velocity decreases. Similarly, the younger and middle aged participants showed negative correlation between error deviation in joint position sense of hip joint and COM displacement. However, when comparing the relationship between joint position sense acuity on lifting postural stability across all thirty-six participants, the results did not show significant relationship between the variables.